Standard handbook of environmental engineering - Corbitt, Robert A. (McGraw-Hill handbooks, 1999)
Written by 36 leading experts in the field, this ""hands-on"" reference provides complete coverage of the latest environmental engineering practices, and includes up-to-date information on legislation and quality criteria to help you establish and prioritize your work goals and objectives. Packed with over 900 tables, charts, and drawings, the Handbook covers air quality control, water supply, wastewater disposal, solid waste management, storm-water, and hazardous waste management. It's a must-have reference for anyone who needs to understand, manage, or evaluate environmental engineering technology.